(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article aims at highlighting one of the most Being a very important aspect of humans’ lives, linguistic politeness has become is the central concern of many scholars in different fields of studies including pragmatics, sociolinguistics, cultural studies, comparative/ contrastive studies and so forth. It is, therefore, no surprise to see a variety of definitions of this phenomenon, however, the one proposed by Brown and Levinson is most widely accepted. Utilizing the notion of “face”, “politeness” is regarded by the researchers as having a dual nature: “positive politeness” indicating similarities amongst interlocutors or expressing an appreciation of the interlocutor’s self-image and “negative politeness” saving the interlocutor’s “face” (either “negative” or “positive”) by mitigating face threatening acts, such as advice-giving and disapproval, or satisfying “negative face” by indicating respect for the addressee’s right not to be imposed on. There are 15 strategies of positive politeness: notice, attend to the hearer, exaggerate, intensify interest to the hearer, use in-group identity markers, seek agreement, avoid disagreement, presuppose / raise / assert common ground, joke, assert or presuppose the speaker’s knowledge and concern for the hearer’s wants, offer / promise, be optimistic, include both the speaker and the hearer, give reasons, assume or assert reciprocity and give gifts to the hearer. Brown and Levinson list the following 10 strategies that make use of negative politeness: be conventionally indirect, question, hedge, be pessimistic, minimize the imposition, give deference, apologize, impersonalize the speaker and the hearer, state the face threatening acts as a general rule, nominalize, go on record as incurring a debt, or as not indebting.